A new species Ficus subg. Ficus (Moraceae) from Thailand and two new records of Ficus species - Berg, Cornelis C.; Gardner, Simon (Thai Forest Bulletin (Botany), 2014)
The new species Ficus thailandica C.C.Berg & S.Gardner is described and two new Ficus records for Thailand detailed.